Dr. Morton Henry Prince, Professor Diseases of the Nervous System, Tufts College Medical School. - Sargent, John Singer. (Tufts University. Tisch Library., 2017)
Abstract: Dr. Morton Henry Prince, prominent Boston physician Born in 1854, Prince attended Boston Latin and Harvard University and became a specialist in nervous diseases and abnormal psychology. Dr. Prince was appointed Professor Diseases of the Nervous System at Tufts College Medical School in 1902, and went on to establish the Journal of Abnormal Psychology in 1908. In 1910 Prince was awarded an honorary degree from Tufts College. John Singer Sargent (1856-1925), was known as a master portrait painter among the upper echelon of society in Europe and the United States. With his impressionist technique that combined elements of light and color, Sargent's figures emitted a rare immediacy and presence of character. See similar portrait AI41510. Date created: 1895. Medium: Oil on canvas. Measurements in inches: 27.375 H. x 22.375 W.